2007
DOI: 10.1210/en.2006-1012
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Activates a Protein Phosphatase-1-Mediated Signaling Pathway to Enhance Overall Translation in Pancreatic β-Cells

Abstract: Both the rate of overall translation and the specific acceleration of proinsulin synthesis are known to be glucose-regulated processes in the beta-cell. In this study, we propose that glucose-induced stimulation of overall translation in beta-cells depends on a protein phosphatase-1-mediated decrease in serine-51 phosphorylation of eukaryotic translation initiation factor 2alpha (eIF2alpha), a pivotal translation initiation factor. The decrease was rapid and detectable within 15 min and proportional to the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 40 publications
9
59
0
Order By: Relevance
“…In low glucose, some hallmarks of the integrated stress response (ISR) were induced, including CHOP and cell death, while ATF6 was not increased (Figure 4, A, B, L, and Supplemental Figure 4C). Our findings are consistent with prior observations that ISR is activated in rat islets or the murine min6 pancreatic β cell line at 2 mM and 5 mM glucose, whereas UPR is activated in high glucose (58,59 F1804). Blots were developed using ECL, ECL prime (GE Healthcare) or SuperSignal West Femto Maximum Sensitivity Substrate (Thermo Scientific).…”
Section: Methodssupporting
confidence: 93%
“…In low glucose, some hallmarks of the integrated stress response (ISR) were induced, including CHOP and cell death, while ATF6 was not increased (Figure 4, A, B, L, and Supplemental Figure 4C). Our findings are consistent with prior observations that ISR is activated in rat islets or the murine min6 pancreatic β cell line at 2 mM and 5 mM glucose, whereas UPR is activated in high glucose (58,59 F1804). Blots were developed using ECL, ECL prime (GE Healthcare) or SuperSignal West Femto Maximum Sensitivity Substrate (Thermo Scientific).…”
Section: Methodssupporting
confidence: 93%
“…Please also note that changes in mRNA levels may result from altered transcription or mRNA stability and that the higher level of complexity due to alternative mRNA splicing was not addressed. Finally, changes in mRNA levels may not necessarily lead to parallel changes in protein levels, as glucose influences general translation as well as translation of specific mRNAs by various mechanisms [39,40].…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been shown that glucose starvation can have a suppressive effect on translation under normoxic conditions in certain cell lines (Gomez et al 2004;Vander Mierde et al 2007) we wanted to determine if the translational repression that we observe under hypoxic conditions is merely a consequence of glucose depletion. Our data clearly show that short-term (20 h) glucose depletion under normoxic conditions has little impact on protein synthesis while dramatically inhibiting translation under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%